The Influence Of Social Media Among Teenagers - Diyana Nur Norazman; Immie Rozianie Abd Rahim (Human Sustainability Procedia, 2022)
This study aimed to form a model in describing the relationship between the variables. This research also seeks to identify the types of social media being used by teenagers and the relationship between the influence of social media and behaviour change among teenagers. This study applied the Theory of Planned Behaviour as the main theory. Quantitative methods were applied in this study and data were collected through the distribution of questionnaires to 210 respondents. In addition, the findings showed the type of social media that were used by teenagers. It is also found that a significant relationship between the influence of social media and behaviour change among teenagers. Hence, this study contributes to the field of communication through the establishment of a more comprehensive variables related to behaviour change among teenagers and help to developed the Planned Behavior Theory.